Growth in animals - Lawrence, T. L. J. (Tony Leonard John) (Studies in the agricultural and food sciences., 1980)
Studies in the Agricultural and Food Sciences: Growth in Animals discusses the more advanced concepts of growth, its changes and effects on different animals and systems, and its implications for agriculture. Based on a symposium of the same name, the book defines growth and its effects on the whole body; the biochemical and genetic determinants that affect it; and the effect of thermal environment on growth and its relation with immunity. Growth of bones, muscle nucleic acid and protein, and adipose tissue are also explained. The text also encompasses the relation of growth and gut microflora.